THE APPROACH TO DEVELOPMENT OF THE ELEMENTS OF THE STRUCTURE OF THE DESTRUCTIVE IMPACT DETECTION SYSTEM IN CYBER SPACE - Соколов, Костянтин Олександрович; Гудима, Олег Петрович (Science-based technologies, 2019)
The article addresses the problematic issue of analyzing information and detecting destructive effects in cyberspace. With the increasing number of users of social information network services every year, and given the significant advantages of the global information environment over conventional media and technologies, issues of information and cyber security in electronic media (cyberspace) in the world where appropriate organizational structures to counteract the hybrid organization Typically, an increase in the amount and density of the destructive information flow (destructive effects) and their types is accomplished by an increase in the structure elements for their intended purpose and the level that generates al structures are created. threats. This requires the creation of appropriate structures in Ukraine. information redundancy for processing. The above does not allow to realize prompt detection of destructive effects (destructive cyberdias), dynamic redistribution of limited forces and means of observation and actions taking into account the level of realization and efficiency of current tasks and informativeness and availability of sources of data about the external situation and preventing the functioning of information conditions, can disrupt the adversary's cyber response targets. Given the above, the purpose of the article is to highlight the approach to building elements of the structure of the system of detection of destructive impact (destructive cyberdias) in cyberspace within the creation in the Ministry of Defense of Ukraine and the Armed Forces of Ukraine of the appropriate System (organizational structure) and will focus on its element, which implements to identify and evaluate destructive effects. Based on the defined criteria and taking into account the indicators of destructive impact, the structure of the element of the system of detection of destructive influence in electronic media (cyberspace) for the detection and evaluation of destructive influence is formed.